Analisis Nilai–Nilai Karakter Siswa Kelas IV di SDN 1 Nyiur Tebel Sukamulia Lombok Timur - Lizatul Aini; Mohammad Liwa Ilhamdi; Radiusman (Mataram University, 2026)
This study aimed to analyze the character values of fourth-grade students at SDN 1 Nyiur Tebel, Sukamulia District, East Lombok Regency. This study employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest model. The research subjects consisted of 30 fourth-grade students selected using a saturated sampling technique. Data were collected through questionnaires and observations using a character values questionnaire consisting of 20 valid and reliable statement items. The data were analyzed using descriptive percentage analysis, the Shapiro-Wilk normality test, and the Paired Sample T-Test with the assistance of IBM SPSS version 31. The results showed that the average score of students’ character values increased from 57.20 in the pretest to 63.83 in the posttest. The normality test results indicated that both pretest and posttest data were normally distributed, with significance values of 0.092 and 0.068 (> 0.05), respectively. The hypothesis test using the Paired Sample T-Test revealed a t-value of -6.854 with a significance value of < 0.001, indicating a significant difference between the pretest and posttest scores. Improvements in character values were observed in the indicators of environmental care, responsibility, honesty, discipline, friendliness/communicativeness, curiosity, democracy, and independence. Observation results also showed positive behavioral development among students during the IPAS learning process. In conclusion, learning activities carried out consistently and systematically contributed positively to improving the character values of fourth-grade students at SDN 1 Nyiur Tebel. The findings of this study imply that IPAS learning can be used as an effective strategy to strengthen character education in elementary schools and assist teachers in integrating character values into classroom learning activities.